Efeito protetor da berberina no dano cerebral, deficit de memória, estresse oxidativo e inflamação de camundongos submetidos à isquemia cerebral focal permanente - Neves, Julliana Catharina de Sousa (2012)
Stroke is the second leading cause death in industrialized countries and can be subdivided into 2 categories, ischemic and hemorrhagic. The mechanisms of ischemic brain damage involve oxidative stress, excitotoxicity, mitochondrial dysfunction, inflammation and apoptosis. Berberine (BE) is an alkaloid derived from Coptidis rhizom which has potent anti-inflammatory and anti-apoptotic effects. In present study, the neuroprotector effect of berberine after permanent middle cerebral artery occlusion (MCAO) was investigated. Male Swiss mice were divided into five groups (n=8): Sham operated (SO), MCAO, BE 50 and 100mg/kg/day plus MCAO. BE or vehicle (distilled water) were administrated intragastrically 30 min before MCAO (induced by electrocoagulation) and daily during 3 days. The parameters studied were sensorimotor function, working, object recognition, spatial and aversive memory, cerebral infarct area, myeloperoxidase (MPO) and reduced glutathione (GSH) levels and neurodegeneration through FluoroJade C staining. After MCAO a significant decrease of motor performance and sensory function was found after a neurological evaluation. However, berberine did not improve this neurological deficit. Ischemia caused a 70% increase of infarct area in MCAO group compared with SO, that was decreased by treatment with BE 50 and 100. We observed an increase of vertical exploratory activity (rearings) in the BE 100 group compared to the MCAO. BE 100 treatment also improved MCAO-induced late memory deficits in passive avoidance test (latency - SO: 235.0 ± 33.3s; MCAO: 84.7 ± 23.3s; MCAO + BE100: 300.0 ± 0.0s, p<0.05) and MCAO-induced spatial memory deficits evaluated by water maze test (latency - SO: 10.8 ± 2.4%; MCAO: 23.4 ± 3.9%; MCAO + BE100: 12.8 ± 2.0; p<0.05). BE 50 and 100 treatment significantly prevented the MCAO-induced working memory deficits in y-maze test (spontaneous alternations - SO: 73.8 ± 1.9%; MCAO: 57.2 ± 2.7%; MCAO + BE50: 69.3 ± 3.5; MCAO + BE100: 71.9 ± 3.97%; p<0.05) and object recognition memory deficits (recognition index - SO: 0.51 ± 0.09%; MCAO: 0.068 ± 0.12%; MCAO + BE50: 0.42 ± 0.09%; MCAO + BE100: 0.58 ± 0.16%; p<0.05, Kruskall-Wallis, Mann-Whitney). Neuronal degeneration on berberine-treated groups was significantly less than those submitted to MCAO. Mice submitted to MCAO showed an increase in GSH and MPO levels. BE 100 treatment prevented the increase in MPO activity on striatum (SO: 1.53 ± 0.48; MCAO: 4.89 ± 0.89; MCAO + BE100: 2.52 ± 0.47; p<0.05, ANOVA, Newman-Keuls). Berberine showed a significant protective effect against cerebral ischemia, at least by an anti-inflammatory effect.